Resemblance of religion and pervasive games: A study among church employees and gamers - Laato Samuli; Rauti Sampsa; Hamari Juho (United States, 2025)
Previous research suggests that the experience and practices related to gaming and extended realities, and religion and spiritualism, share similarities. In this study, we explore how both the employees of the Evangelical Lutheran Church (n=156) and pervasive game players (n=98) perceive and make sense of these connections. We approach the qualitative data from the perspective of Durkheim, who, similarly to how game theorists view games, views religion as a multi-faceted system that incorporates the rules, practices and communities that comprise the religion. From the data emerges the following prominent connection as perceived by both groups of informants: systems of (1) shared premise, (2) resilience and restoration, (3) symbolism, (4) extended reality and (5) day-to-day structuring. A numerical view of the data shows that 42,5% of the participants did not perceive similarities, and examination of these responses suggested that while religion and pervasive games share functional similarities, they are further apart from a substantive perspective.
CHI '23: Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems